Strategi Penguatan Keterampilan Berbahasa Arab Siswa Sekolah Dasar Berbasis Tahfizh Qur’an - Apri Wardana Ritonga; Desriliwa Ade Mela; Ayu Desrani (Institut Agama Islam Tribakti Kediri, 2022)
The rapid development of globalization has made global competition even tougher. Improving language skills has become a necessity for everyone, including Arabic. Arabic is important to be taught to students since they are in elementary school so that Arabic will be a provision for them when they grow up, one of which is to study religious knowledge. This study aimed to describe the strategy of strengthening Arabic skills of elementary school students based on tahfizh Qur'an. This study adopted a descriptive qualitative approach with a case study method at SD Tahfizh Al-Qur'an Daarul Ukhuwwah Malang. Data collection techniques through observation, interviews, and documentation. The collected data is then analyzed through the stages of reduction, presentation, and verification or drawing conclusions. The results of this study indicate that: a) game-based Arabic learning strategies to attract students' attention to learning; b) the Arabic language learning program must be followed by teachers and students, teacher activities are directly guided by the principal, while the student program is guided by the teacher in the form of making Arabic videos, Arabic songs, and depositing Arabic vocabulary via Whatsapp; c) obstacles found during the learning process in the form of student delays when depositing Arabic vocabulary due to lack of parental supervision and motivationThe findings of this study reveal the positive impact that arises from the game-based Arabic learning process, namely that students are able to communicate Arabic with their teachers and friends. [Perkembangan arus globalisasi yang semakin cepat, membuat persaingan global juga semakin ketat. Meningkatkan keterampilan berbahasa sudah menjadi keniscayaan bagi semua orang termasuk bahasa Arab. Bahasa Arab penting untuk diajarkan pada siswa sejak mereka duduk di bangku Sekolah Dasar agar bahasa Arab menjadi bekal bagi mereka ketika beranjak dewasa salah satunya untuk mempelajari ilmu agama. Penelitian ini bertujuan untuk mendeskripsikan strategi penguatan keterampilan berbahasa Arab siswa sekolah dasar bebasis tahfizh Qur’an. Penelitian ini mengadopsi pendekatan kualitatif deskriptif dengan metode studi kasus di SD Tahfizh Al-Qur’an Daarul Ukhuwwah Malang. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Data yang terkumpul kemudian dianalisis melalui tahapan reduksi, penyajian, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa: a) strategi belajar sambil bermain sangat menarik perhatian siswa dalam pembelajaran bahasa arab; b) program pembelajaran bahasa Arab wajib diikuti oleh guru dan siswa, kegiatan guru dibimbing langsung oleh kepala sekolah, sedangkan program siswa dibimbing oleh guru berupa pembuatan video bahasa Arab, lagu bahasa Arab, dan setoran kosa-kata bahasa Arab melalui Whatsapp; c) kendala yang ditemukan saat proses pembelajaran berupa keterlambatan siswa saat setoran kosa-kata bahasa Arab karena kurangnya pengawasan dan motivasi orang tua. Temuan penelitian ini mengungkap dampak positif yang muncul dari proses pembelajaran bahasa Arab berbasis games yaitu siswa mampu berkomunikasi bahasa arab dengan guru maupun temannya]